2016
DOI: 10.4314/ajtcam.v13i2.19
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-mimetic activity of stevioside on diabetic rats: biochemical, molecular and histopathological study

Abstract: Background: Stevioside has been used as a medication for reducing glucose levels in diabetic patients. The exact mode of action is still unclear. Therefore, the current study outlined the molecular and biological roles of stevioside in treatment of diabetes. Materials and Methods: Diabetic male Wistar rats were treated with stevioside and metformin as a medication for diabetes rats for 4 weeks. Biochemical, molecular and histopathological studies have been done to evaluate the therapeutic effect of stevioside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
2
0
1
Order By: Relevance
“…The results are in collaborations with the studies conducted by Shivanna et al [ 39 ]; Saleh et al [ 40 ] and Abou khalil et al [ 41 ] who concluded that aqueous extracts of Stevia rebaudiana leaves and Desert date ( Balanites aegyptiaca ) and Parsley ( Petroselinum sativum ) stevioside normalize the pancreatic cell function by restoring the insulin immune reactivity in STZ-induced diabetic rats.…”
Section: Discussionsupporting
confidence: 80%
“…The results are in collaborations with the studies conducted by Shivanna et al [ 39 ]; Saleh et al [ 40 ] and Abou khalil et al [ 41 ] who concluded that aqueous extracts of Stevia rebaudiana leaves and Desert date ( Balanites aegyptiaca ) and Parsley ( Petroselinum sativum ) stevioside normalize the pancreatic cell function by restoring the insulin immune reactivity in STZ-induced diabetic rats.…”
Section: Discussionsupporting
confidence: 80%
“…Group 2 supplemented with camel milk (CM). Diabetes was induced in the remaining forty-five rats by intraperitoneal injection of STZ (60 mg/kg bw, Sigma-Aldrich St. Louis, MO, USA) based on protocol stated by Saleh et al (2016). To avoid the sudden death of the diabetic rats due to hypoglycemia, rats were supplemented with 5% glucose solution for the next 12 h following STZ injection.…”
Section: Experimental Designmentioning
confidence: 99%
“…Therefore, Stevia plays a key role in the regulation of these processes [ 27 ]. Stevia rebaudiana is an important component in food processing including fruit juices, baked products, tobacco derivatives, chewing gums, candies, pickles, coffee, and mostly beverages [ 28 ].…”
Section: Introductionmentioning
confidence: 99%